Coordination of MicroRNAs, PhasiRNAs, and NB‐LRR Genes in Response to a Plant Pathogen: Insights from Analyses of a Set of Soybean Rps Gene Near‐Isogenic Lines. Issue 1 (1st March 2015) - Zhao, Meixia; Cai, Chunmei; Zhai, Jixian; Lin, Feng; Li, Linghong; Shreve, Jacob; Thimmapuram, Jyothi; Hughes, Teresa J.; Meyers, Blake C.; Ma, Jianxin
Abstract : Disease‐related genes, particularly the nucleotide binding site (NB)–leucine‐rich repeat (LRR) class of R plant genes can be triggered by microRNAs (miRNAs) to generate phased small interfering RNAs (phasiRNAs), which could reduce the transcript levels of their targets. However, how global changes in NB‐LRR transcript levels coordinate with changes in miRNA and phasiRNA levels in defense responses remains largely unknown. Here, we investigated changes in the relative abundance of small RNAs (sRNAs), with a focus on miRNAs and phasiRNAs and their potential targets in response to the pathogen Phytophthora sojae in the susceptible soybean [Glycine max (L.) Merr.] 'Williams' and nine resistant near‐isogenic lines (NILs), each carrying a unique resistance to P. sojae ( Rps ) gene. In total, 369 distinct miRNAs, including 78 new ones, were identified in the 10 soybean lines. The majority of miRNAs were downregulated by the pathogen. Of the 525 NB‐LRR genes found in the soybean reference genome, 257 were predicted to be the targets of eight abundant miRNA families and 126 (dubbed phasi‐NB‐LRRs or pNLs ) were predicted to have produced phasiRNAs. Upregulation of 15 phasi‐NB‐LRRs was associated with downregulation of their corresponding phasiRNAs in the NILs; these phasiRNAs were predicted to regulate 75 additional NB‐LRR s in trans . In addition, we identified putative 24‐nucleotide (nt) phasiRNAs from transposons, possibly representing a novel general epigenetic mechanism for regulation of transposon activity under biotic stresses. Together, these observations suggest that miRNAs and phasiRNAs play an important role in response to plant pathogens through complex, multiple layers of post‐transcriptional regulation.